2007
DOI: 10.7326/0003-4819-147-6-200709180-00006
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Contraception and Pregnancy When Prescribing Potentially Teratogenic Medications for Reproductive-Age Women

Abstract: Background-Certain medications are identified by the U.S. Food and Drug Administration (FDA) as class D or X because they increase the risk for birth defects if used during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 18 publications
1
68
0
6
Order By: Relevance
“…To communicate the potential teratogenic risk of a medication to the prescriber, the US Food and Drug Administration (FDA) currently uses an evidence-based grading system as part of product labeling that categorizes medications by potential for teratogenic risk (eg, category A are those with no demonstrated risk, categories D and X are those associated with definite risk and positive evidence of fetal harm). 1 Several studies of family and internal medicine providers demonstrated low rates (20%-48%) of contraception provision among females of reproductive age prescribed teratogens. [1][2][3][4] However, no previous study has evaluated practices among pediatric providers or examined rates of documentation of sexual history or menstrual history in adolescents prescribed teratogens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To communicate the potential teratogenic risk of a medication to the prescriber, the US Food and Drug Administration (FDA) currently uses an evidence-based grading system as part of product labeling that categorizes medications by potential for teratogenic risk (eg, category A are those with no demonstrated risk, categories D and X are those associated with definite risk and positive evidence of fetal harm). 1 Several studies of family and internal medicine providers demonstrated low rates (20%-48%) of contraception provision among females of reproductive age prescribed teratogens. [1][2][3][4] However, no previous study has evaluated practices among pediatric providers or examined rates of documentation of sexual history or menstrual history in adolescents prescribed teratogens.…”
mentioning
confidence: 99%
“…1 Several studies of family and internal medicine providers demonstrated low rates (20%-48%) of contraception provision among females of reproductive age prescribed teratogens. [1][2][3][4] However, no previous study has evaluated practices among pediatric providers or examined rates of documentation of sexual history or menstrual history in adolescents prescribed teratogens. To address this knowledge gap, we conducted a targeted, retrospective assessment of contraception provision in a large cohort of adolescent females prescribed potential teratogens.…”
mentioning
confidence: 99%
“…11,12 No caso particular da isotretinoína, considerada o retinói-de de eleição em mulheres em idade fértil, recomenda-se a exclusão da gravidez antes do início do tratamento, a utilização em simultâneo de duas formas de contraceção durante o tratamento, a execução de testes de gravidez sempre que ocorrer alguma falha nas medidas contracetivas e que se adie qualquer tentativa de engravidar até pelo menos três meses desde a sua suspensão. 13,14 O uso de isotretinoína durante o aleitamento está também contra-indicado pois as concentrações no leite são significativas. 15 Em virtude da sua imaturidade renal e hepática, os níveis séricos nos lactentes poderiam atingir níveis tóxicos, predispondo a complicações como hepatotoxicidade, aumento da pressão intracraniana, dores ósseas e articulares, e aumento do risco de infeção respiratória.…”
Section: Retinóides Sistémicos (Categoria De Risco X Pela Fda)unclassified
“…В таких случаях требуется информировать женщин не только о частоте и тяжести тератогенных эффектов, но также об альтернативной терапии с менее выражен-ными фетальными эффектами. Продемонстрировано, что врачебная консультация по поводу применения кон-трацептивов может способствовать увеличению знаний женщин о связанных с беременностью рисках, изменяя их поведение и уменьшая экспозицию тератогенами во время беременности [34,35]. Однако, в ряде работ это не нашло подтверждения для улучшения исходов беременности [36,37].…”
Section: информационное обеспечение доказательности безопасного исполunclassified